Hubungan Pola Makan dengan Kadar Gula Darah Pasien DM Tipe 2 di Rumah Sakit Sari Asih Karawaci - Nur Khaira Rahmadhani; Nutrisia Nu’im Haiya; Moch. Aspihan (Jurnal Siti Rufaidah, 2026)
Type 2 Diabetes Mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin action. Blood glucose control is influenced by various factors, one of which is dietary patterns. Diets that do not adhere to balanced nutrition principles can lead to poor glycemic control and increase the risk of complications. This study employed a quantitative design with a cross-sectional approach. The research sample consisted of 95 patients with Type 2 Diabetes Mellitus at Sari Asih Karawaci Hospital in 2025, selected using purposive sampling techniques. Dietary pattern data were collected using a questionnaire, while blood glucose level data were obtained from medical examination results. Data analysis was conducted using univariate and bivariate analysis with the Contingency Coefficient test. The results showed that most respondents had good dietary patterns (58.9%), and blood glucose levels within the normal category (51.6%). Bivariate analysis using the Contingency Coefficient test indicated a p-value of 0.005, demonstrating a significant relationship between dietary patterns and blood glucose levels in patients with Type 2 Diabetes Mellitus. There is a significant relationship between dietary patterns and blood glucose levels in patients with Type 2 Diabetes Mellitus. Proper dietary management is an important factor in controlling blood glucose levels and should be a primary focus in nursing care and health education for patients with Type 2 Diabetes Mellitus.